Sequential Cerebrospinal Fluid Sampling in Horses: Comparison of Sampling Times and Two Different Collection Sites - Andrade, Danilo Giorgi Abranches de [UNESP]; Cerri, Fabrício Moreira [UNESP]; Barbosa, Giovanna Valverde Magalhães [UNESP]; Basso, Roberta Martins [UNESP]; Takahira, Regina Kiomi [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Oliveira-Filho, José Paes de [UNESP]; Borges, Alexandre Secorun [UNESP] (Elsevier, 2022)
Analysis of the cerebrospinal fluid (CSF) is important as a complementary test in horses with neurologic diseases, and sequential analysis may provide information about the treatment response or evolution and quantitative measures of the CSF drug concentration during treatment. The aim of this study was to compare erythrocyte and nucleated cell counts and protein concentration in multiple CSF samples obtained sequentially from two different puncture sites in clinically healthy horses. Eight and 12 horses, with no evidence of neurologic disease, were subjected to CSF collection from the atlanto-occipital (AO) and C1–C2 spaces, respectively. Cytologic and chemical analyses were performed on the CSF obtained at five sampling times (T1, T2, T3, T4, and T5). Repeated measures models were used to compare the mean erythrocyte count, nucleated cell count, and total protein concentration between the AO and C1–C2 groups at each sampling time. C1–C2 CSF had a significantly higher total protein concentration at T1 and T4 than that of AO CSF. All total protein concentration values remained within the reference interval (<90 mg/dL) for all sampling times and groups. No statistical difference was present between results at T2, T3, T4, and T5 and at T1 in both groups for all analyses. In conclusion, five consecutive AO or C1–C2 CSF collections with at least a 7-d interval did not result in alterations in the CSF erythrocyte and nucleated cell counts and total protein concentrations and did not interfere with the CSF analysis results.
Keywords: Atlanto-occipital; Cervical; CSF collection; Equine; Neurologic disease